Teaching in the field : working with students in the outdoor classroom - Crimmel, Hal, 1966- (Salt Lake City : University of Utah Press, 2003)
A collection of essays that examine the effectiveness of teaching students in alternate classroom environments and present pedagogical strategies and foundational advice based on the field studies of colleges and universities.
Includes bibliographical references and index.
Adult
Keywords: Fieldwork (Educational method); Literature -- Study and teaching (Higher); Outdoor education; Literature -- Study and teaching; Outdoor education; Project method in teaching